Computer-based simulation of plasma concentration time-profiles of drug in nonlinear two-compartment model - Piekarski, Sławomir; Kiełczyński, Piotr; Szalewski, Marek; Rewekant, Mirosław (Computer Assisted Methods in Engineering and Science; Vol 20 No 4 (2013), 2017)
The main interest of pharmacokinetics is the study of the fate of drugs in the living organism. This work proposes the system of the conservation laws that describes time-dependent concentrations of a drug, after a single intravenous administration. Compared with others, the proposed model considers both free and protein-bound drug concentrations at the same time. Plasma protein binding captured in the model enters the nonlinearity arising from the Guldberg-Waage law. According to our best knowledge, the analytical solution for our system does not exist. Our model allows the calculation of the free and bound-drug protein concentrations at any time point and at any dose after single intravenous bolus dose administration. In order to compare the empirical with simulated data, a numerical approach has been proposed. On the basis of published experimental data the model validation has been carried out. The goodness of fit was satisfactory ( R ² = 0.99) and the experimental and simulated AUC (area under the curve) values, as the measure of the bioavailability of drug, were similar (150 M/hxh - ¹). The preliminary assessment of the model credibility was positive and encouraged further studies.